2018
DOI: 10.1038/s41416-018-0038-5
|View full text |Cite
|
Sign up to set email alerts
|

The multifunctional solute carrier 3A2 (SLC3A2) confers a poor prognosis in the highly proliferative breast cancer subtypes

Abstract: Breast cancer (BC) is a heterogeneous disease characterised by variant biology, metabolic activity and patient outcome. This study aimed to evaluate the biological and prognostic value of the membrane solute carrier, SLC3A2 in BC with emphasis on the intrinsic molecular subtypes. SLC3A2 was assessed at the genomic level, using METABRIC data (n = 1980), and at the proteomic level, using immunohistochemistry on tissue microarray (TMA) sections constructed from a large well-characterised primary BC cohort (n = 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…SLC7A5 requires a covalent association with the heavy chain of the membrane protein, solute carrier family 3 member 2 (SLC3A2), for its functional expression in plasma membrane [13]. We have previously described the potential utility of these two solute carriers as prognostic factors for the highly proliferative BC subtypes [14,15]. Additionally, other studies have revealed the prognostic value of the co-operative expression of SLC7A5 and SLC3A2 in transitional cell carcinoma [16], squamous cell carcinoma of the lung [17] and pulmonary adenocarcinoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…SLC7A5 requires a covalent association with the heavy chain of the membrane protein, solute carrier family 3 member 2 (SLC3A2), for its functional expression in plasma membrane [13]. We have previously described the potential utility of these two solute carriers as prognostic factors for the highly proliferative BC subtypes [14,15]. Additionally, other studies have revealed the prognostic value of the co-operative expression of SLC7A5 and SLC3A2 in transitional cell carcinoma [16], squamous cell carcinoma of the lung [17] and pulmonary adenocarcinoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly interesting as the luminal B subtype (ER+ subtype) has aggressive clinical behavior, with prognosis similar to that of HER2-enriched and basal-like group and a lower sensitivity to endocrine treatment compared to luminal A ER+ breast cancer (59). Interestingly, recent studies showed that a high expression of different AA transporters, such as SLC3A2 or SLC7A5, is related to poor outcomes in luminal B ER+ breast cancer subtype (60, 61). These data suggest that this subtype might be particular vulnerable to glutamine depletion.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these biological functions, overexpression of CD98hc has been observed in various solid and hematological malignancies, such as non‐small cell lung cancer (NSCLC), breast cancer, colorectal cancer and acute myeloid leukemia (AML) . In general, the overexpression of CD98 is associated with poor prognosis for cancer patients, thus rendering it a promising tumor target for diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%